The Effects of Anesthetic Technique on Postoperative Opioid Consumption in Ankle Fracture Surgery. Issue 10 (October 2016) - Christensen, Kristian P.; Møller, Ann M.; Nielsen, Jesper K.; Klausen, Tobias W.; Sort, Rune
Abstract : Objectives: To investigate the impact of common anesthetic techniques on postoperative opioid consumption in ankle fracture surgery. Materials and Methods: We performed a retrospective cohort study on 622 patients with isolated ankle fractures undergoing primary reconstructive surgery. Patients were identified by consecutive screening in the years 2008 to 2011. Our primary endpoint was the difference in the 24-hour postoperative opioid consumption after general anesthesia (GA) compared with different regional anesthesia modalities. Secondary endpoints were length of stay in the postanesthesia care unit, risk of postoperative nausea and vomiting, and postoperative length of hospital stay. Results: Opioid consumption in 4 anesthesia groups (equipotent doses of IV morphine) was as follows: GA: 21.9 mg (95% confidence interval [CI]±1.2), GA+peripheral nerve block (PNB): 16.3 mg (95% CI±1.1), spinal anesthesia (SA): 17.1 mg (95% CI±0.9), and SA+PNB: 14.6 mg (95% CI±1.0). We found significant differences between "GA" and all other groups ( P ⩽0.01). The most pronounced difference is seen when GA is compared with SA+PNB, with a 33.4% opioid reduction in the latter group. Discussion: Regional anesthesia modalities reduce postoperative opioid consumption in ankle fracture surgery in comparison with GA. A benefit of PNBs is possibly due to an improved pain profile. Our study is retrospective and cannot predict the exact magnitude of this benefit.